2020
DOI: 10.1038/s41598-020-75971-0
|View full text |Cite
|
Sign up to set email alerts
|

Long-term N fertilization reduces uptake of N from fertilizer and increases the uptake of N from soil

Abstract: Long-term supply of synthetic nitrogen (N) has the potential to affect the soil N processes. This study aimed to (i) establish N response curves to find the best balance between inputs and outputs of N over four ratoons; (ii) use 15N-labeled fertilizer to estimate the N recovery efficiency of fertilizer applied in the current season as affected by the N management in the previous three years. Nitrogen rates (control, 60, 120, and 180 kg ha−1 N) were applied annually in the same plots after the 1st, 2nd, 3rd, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 55 publications
1
1
0
2
Order By: Relevance
“…Overall, with the increasing years of greenhouse vegetable cultivation, both average relative plant N uptake and average NUE decreased markedly (Figure 6a,b). The result was consistent with that of Joris et al [34], who found that long-term fertilization reduced the uptake of N from fertilizer and increased the uptake of N from the soil. Similarly, Van et al [33] found that the sufficient plant-available original N in soil over the growing season would result in limited yield response to fertilized N. This means that in soil with a higher capacity for N supply, the contribution of exogenous N to plant N uptake was not as much as that in soil with lower capacity for N supply, because plant growth depended more on the soil-derived N. This result also confirmed the fact that the NUE present in our research was higher than the real value due to the interference of soil-derived N. The gap between them might increase with the increasing years of greenhouse vegetable cultivation.…”
Section: N Uptake Residue and Lossessupporting
confidence: 93%
See 1 more Smart Citation
“…Overall, with the increasing years of greenhouse vegetable cultivation, both average relative plant N uptake and average NUE decreased markedly (Figure 6a,b). The result was consistent with that of Joris et al [34], who found that long-term fertilization reduced the uptake of N from fertilizer and increased the uptake of N from the soil. Similarly, Van et al [33] found that the sufficient plant-available original N in soil over the growing season would result in limited yield response to fertilized N. This means that in soil with a higher capacity for N supply, the contribution of exogenous N to plant N uptake was not as much as that in soil with lower capacity for N supply, because plant growth depended more on the soil-derived N. This result also confirmed the fact that the NUE present in our research was higher than the real value due to the interference of soil-derived N. The gap between them might increase with the increasing years of greenhouse vegetable cultivation.…”
Section: N Uptake Residue and Lossessupporting
confidence: 93%
“…Research by Liang et al [31,32] reported that the long-term co-application of organic materials with chemical fertilizers (instead of no fertilizer or merely chemical fertilizers) improved the synchrony between N supply and crop demand, thus increasing N use efficiency while reducing N losses from the system. Further research found that the sufficient plant-available original N in soil over the growing season would result in a limited crop response to fertilized N by increasing the contribution of soil derived N [33,34]. However, how the effects of fertilization practices would change with the cultivation years of greenhouse vegetables is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Estes resultados indicam que os manejos podem se sobressair independente da combinação com outras práticas sustentáveis, estando ligados principalmente as condições específicas de cada safra, como as condições ambientais e níveis de fertilidade do solo. Os benefícios proporcionados tanto pela adubação nitrogenada quanto o plantio direto na canade-açúcar, de forma separada ou conjunta, são extensivamente reportados na literatura (Duarte Júnior and Coelho, 2008;Joris et al, 2020;Tenelli et al, 2021). Dentro de um contexto mais amplo, levando em consideração os efeitos experimentais ao longo de três soqueiras, os resultados experimentais deste trabalho mostraram que as doses de N aumentam a biomassa seca (Figura 6b) e produtividade de colmos (Figura 9b), independente do manejo de solo e sucessão de cultura, apresentando dose ótima com reposição de 100 % do N exportado.…”
Section: Discussionunclassified
“…Por outro lado, a sucessão de culturas também afetou a produtividade de colmos e açúcar ao longo de três anos (Figura 9 e 10), apresentando incrementos produtivos com adoção da Crotalaria ochroleuca e níveis produtivos menores para sistemas com amendoim. Embora a combinação desses fatores não foi identificada ao longo das três soqueiras, foi possível mais uma vez confirmar a resposta da reposição de nitrogênio para manutenção da produtividade de soqueiras (Joris et al, 2020).…”
Section: Discussionunclassified